Application of Cultural Diversity Quartet Learning Media to Improve Student Learning Outcomes in Class 4 ES 02 Silaut - Khaira, Ummul; Erita, Yeni; Ovartadara, Maiyona (Postgraduate School, Universitas Negeri Padang, 2023)
This study aims to analyze the increase in learning outcomes for class IV Technical Services Unit (TSU) Elementary School (ES) 02 Silaut students in the 2022/2023 academic year. The research method used is classroom action research. The subjects of this study were 24 students of class IV TSU ES 02 Silaut. The research phase consists of planning, action, observation, and reflection. Data collection methods are interviews, observations, tests, and documentation. Data collection instruments are used in the form of observation, tests, and documentation. The data analysis technique used is descriptive qualitative and quantitative data analysis techniques. Before conducting classroom action research, namely, student learning outcomes in social studies class IV were low. The results showed that the learning outcomes for social studies content averaged 73 in the first cycle with 65% classical completeness, then increased in the second cycle with a significant increase to 82 and 85% classical completeness. While the indicator of success, namely 75%. So, it can be concluded that quartet learning media can improve student learning outcomes in Class IV TSU ES 02 Silaut.